Représentations du trauma dans le roman En vérité de E. Périkléous-Papadopoulou : identités brisées et failles, à travers une métacritique de l’histoire dans la “littérature du devoir de mémoire” - Louisa Christodoulidou (Cahiers Balkaniques)
The words: “MEMORY AND NOSTALGIA” –  in emphatic capital letters – at the opening of the novel by E. Perikelous Papadopoulos, Truly Spoken, are the key concepts around which the narrative thread unfolds concerning the grief of Charita Mantoles and her unending, unequal struggle to seek out the missing truth. The manifest presence of memory and trauma as the dominant thematic motifs, constitutes a heavy burden of mixed joy and sorrow which the heroine has carried ever since the tragic events of the Turkish invasion of 1974. The author constructs an eminently readable novel, incorporating numerous losses and shattering truths, bringing to the surface the central heroine’s vulnerabilities. History (signified) is closely combined with imagination to create a compelling fiction based on real events. As a result, it presents a metacritique of history that is at the same time the transcript of an authentic testimony. Accordingly the characters in the novel are seen to evolve in a completely realistic environment.